👤

de ce lim x-> 0 x > 0 din ln x = - infinit?​

Răspuns :

Explicație pas cu pas:

[tex] lim_{x - > 0^{+}}( ln(x) ) = - \infty [/tex]

știm că:

[tex] ln(x) = - ln( \frac{1}{x} ) [/tex]

și că:

[tex]lim_{x - > 0^{+}}( \frac{1}{x} ) = \infty [/tex]

atunci când

[tex]x - > 0,x > 0[/tex]

avem:

[tex] ln( \frac{1}{x} ) - > \infty [/tex]

deci:

[tex] - ln( \frac{1}{x} ) - > - \infty [/tex]

adică:

[tex]ln(x) - > - \infty [/tex]

de unde rezultă că:

[tex] lim_{x - > 0^{+}}( ln(x) ) = - \infty [/tex]

Vezi imaginea Andyilye